Fi’aliyah Istikhdam Tathbiq Educandy ‘ala Taqyim Dirasah al-Lughah al-‘Arabiyyah - Fajr, Ventia Mathla'il; Muslihudin, Muslihudin; Nurhuda, Abid; Qosim, Muhammad Nanang (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2023)
There should be no spelling, grammar, and expression errors in the language used. Most educators at the evaluation stage use the classical method, namely by practicing questions or written exams. However, this concept causes boredom for students so it reduces interest in learning and even affects their learning outcomes. In addition, the development of learning evaluation methods is irrelevant (stagnant). The purpose of this study was to find the effectiveness of the educandy application for evaluating Arabic language learning in terms of learning interest and learning outcomes of class VII students at Islamic Special Madrasah Tsanawiyah at Gondangrejo Karanganyar in 2021. This research included quantitative research using experimental methods. The Pre-Experimental research design used was One Group Pretest-Posttest Design and used purposive sampling in sampling. Then a analyzed the data using the Statistical Product and Service Solution (SPSS) version 16. The results of this study stated that the use of the Educandy application was less effective on student learning outcomes. However, the use of the Educandy application in increasing student interest in learning is considered effective. This is evidenced by the results of the Independent Sample T-Test with a value of 0.72358 0.05 so that H0 is accepted and H1 is rejected.